(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
In this article, we conduct qualitative research on this topic. The study we’re going to present with a qualitative way primary purpose is to focus on understanding English language teacher’s perceptions of using the social disability model to teach visually impaired students. In other words, millions of people are struggling with disabilities problems here in Pakistan, so highlighting this topic is very important. Because doing this it will remind us to do the right things with a better approach to solving the issues.